2015
DOI: 10.1074/jbc.m114.617837
|View full text |Cite
|
Sign up to set email alerts
|

Activated α2-Macroglobulin Binding to Human Prostate Cancer Cells Triggers Insulin-like Responses

Abstract: Background: Ligation of cancer cell surface GRP78 by activated ␣ 2 -macroglobulin (␣ 2 M*) promotes proliferation and blocks apoptosis. Results: ␣ 2 M* treatment of prostate cancer cells enhances the Warburg effect and up-regulates lipid metabolism in an insulinlike manner. Conclusion: ␣ 2 M* exerts insulin-like effects on prostate cancer cells. Significance: Targeting cell surface GRP78-dependent cancer cell regulation, such as by antibodies, offers a unique potential therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Cell surface GRP78 has been implicated in the progression of many human cancers including melanoma, breast, prostate cancer and hepatocellular carcinoma [ 9 ]. Lots of data have linked cell surface GRP78 to pro-proliferative and anti-apoptotic signaling pathway [ 33 ]. However, the role of cell surface GRP78 in tumor invasion and metastasis remains poor documented.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface GRP78 has been implicated in the progression of many human cancers including melanoma, breast, prostate cancer and hepatocellular carcinoma [ 9 ]. Lots of data have linked cell surface GRP78 to pro-proliferative and anti-apoptotic signaling pathway [ 33 ]. However, the role of cell surface GRP78 in tumor invasion and metastasis remains poor documented.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the anticancer potential of fatostatin has been investigated. In prostate cancer cell lines, fatostatin inhibits cell proliferation and insulin-stimulated protein and DNA synthesis (18,40,41). These effects have been attributed to fatostatin inhibition of SCAP-and SREBP-dependent transcription.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Importantly, targeting CS-GRP78 by C38 or other specific monoclonal antibodies inhibits tumor growth in murine xenograft models of various tumors [ 28 , 31 , 35 ]. In addition, recently we reported that the α 2 M * /CS-GRP78 axis regulates metabolic alterations to enhance aerobic glycolysis and induce fatty acid synthesis in prostate cancer cells [ 36 ]. However, it is not known whether the α 2 M * /CS-GRP78 axis contributes to histone acetylation by regulating metabolic reprogramming.…”
Section: Introductionmentioning
confidence: 99%